Socioeconomic inequality in organized and opportunistic screening for gastric cancer: results from the Korean National Cancer Screening Survey 2009–2022 - Luu, Xuan Quy; Lee, Kyeongmin; Jun, Jae Kwan; Suh, Mina; Choi, Kui Son (Frontiers in Public Health, 2023)
Objectives This study aimed to evaluate the socioeconomic inequality in gastric cancer (GC) screening in Korea. Socioeconomic inequality was assessed using both organized and opportunistic screening according to income and educational level. Methods GC screening data were obtained from the 2009–2022 Korean National Cancer Screening Survey. The final analysis included 47,163 cancer-free men and women. The weighted cancer screening rate was estimated using joinpoint regression. The inequality indices were measured in terms of both the absolute slope index of inequality (SII) and the relative index of inequality (RII) using the Poisson regression model. Results The organized screening rate for GC increased from 38.2% in 2009 to 70.8% in 2022, whereas the opportunistic screening rate decreased from 18.8 to 4.5%. Regarding educational inequality, a negative SII value was observed [−3.5, 95% confidence interval (CI), −7.63–0.83%] in organized screening, while a positive SII (9.30%; 95% CI, 6.69–11.91%) and RII (1.98%; 95% CI, 1.59–2.46) were observed in opportunistic screening. Furthermore, income inequality was not found in organized GC screening; however, overall SII and RII for opportunistic screening were 7.72% (95% CI, 5.39–10.5) and 1.61 (95% CI, 1.42–1.81), respectively. Conclusion Organized screening rates have grown gradually over time and account for the majority of GC screenings in South Korea. While no socioeconomic inequalities were found in organized screening, significant socioeconomic inequalities were found in opportunistic screening.